2013
DOI: 10.1038/srep03336
|View full text |Cite
|
Sign up to set email alerts
|

Is Chemically Synthesized Graphene ‘Really’ a Unique Substrate for SERS and Fluorescence Quenching?

Abstract: We demonstrate observation of Raman signals of different analytes adsorbed on carbonaceous materials, such as, chemically reduced graphene, graphene oxide (GO), multi-walled carbon nanotube (MWCNT), graphite and activated carbon. The analytes selected for the study were Rhodamine 6G (R6G) (in resonant conditions), Rhodamine B (RB), Nile blue (NBA), Crystal Violet (CV) and acetaminophen (paracetamol). All the analytes except paracetamol absorb and fluoresce in the visible region. In this article we provide expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 37 publications
(45 reference statements)
7
38
0
Order By: Relevance
“…S1) showed that HU-NaBH 4 existed primarily as large areas of stacked sheets, which is in contrast to the highly exfoliated wrinkled structures seen in HU-TRGO and HU-N 2 H 4 . This morphology is consistent with other studies, in which the surface areas of NaBH 4 -reduced RGOs are distinctly lower than that of hydrazine-reduced RGOs (20,(47)(48)(49). As a result, a large proportion of the Mn-based impurities in HU-NaBH 4 would have been sheathed in between these stacked sheets, rendering them surface-inaccessible and thus, leading to the greatly reduced catalytic effect observed.…”
Section: Resultssupporting
confidence: 91%
“…S1) showed that HU-NaBH 4 existed primarily as large areas of stacked sheets, which is in contrast to the highly exfoliated wrinkled structures seen in HU-TRGO and HU-N 2 H 4 . This morphology is consistent with other studies, in which the surface areas of NaBH 4 -reduced RGOs are distinctly lower than that of hydrazine-reduced RGOs (20,(47)(48)(49). As a result, a large proportion of the Mn-based impurities in HU-NaBH 4 would have been sheathed in between these stacked sheets, rendering them surface-inaccessible and thus, leading to the greatly reduced catalytic effect observed.…”
Section: Resultssupporting
confidence: 91%
“…48,49 Besides graphene, SERS substrates using graphene derivative covered Au or Ag films were also studied. 28,50 Figure 6c 51 shows that octahedral Ag @ GO gives the strongest enhancement of 9.5 × 10 5 , stronger than 6.9 × 10 5 for a Ag nanocube on GO and 1.0 × 10 5 for a Ag nanosphere on GO. In future research, more promising structures are expected for specific applications.…”
Section: Gers Meets With the Metal Substratementioning
confidence: 99%
“…2,7,8 The origin of GERS is still controversial since the electromagnetic enhancement (EE), which is mostly responsible of the high SERS on metallic surfaces, is not as effective on graphene because of the smooth surface and plasmon excitation in the terahertz region. 10 Other mechanisms have been therefore supposed to be the source of GERS, such as chemical enhancement (CE), fluorescence quenching 9 and efficient adsorption. 10 Graphene has a flat and smooth surface particularly suitable for homogeneous deposition of organic molecules, such as aromatics, which can interact through π-π bonding interactions capable of promoting charge transfer and therefore CE.…”
mentioning
confidence: 99%
“…10 Other mechanisms have been therefore supposed to be the source of GERS, such as chemical enhancement (CE), fluorescence quenching 9 and efficient adsorption. 10 Graphene has a flat and smooth surface particularly suitable for homogeneous deposition of organic molecules, such as aromatics, which can interact through π-π bonding interactions capable of promoting charge transfer and therefore CE. On the other hand, it has been demonstrated that graphene is not the only carbon-based platform for the enhancement of Raman signals, and various materials such as graphene oxide, multi-walled carbon nanotubes, graphite and activated carbon also exhibit Enhancement of Raman Scattering (ERS).…”
mentioning
confidence: 99%
See 1 more Smart Citation